Petrogenesis of The Sintang Intrusives and Its Implications for Mineralization In Northwest Kalimantan - Udi Hartono (Pusat Survei Geologi, 2006)
Arc magmatism is a direct response to tectonic and chemical processes operating in subduction zones. The Sintang Intrusives consist of microdiorite, microgranodiorite, granite/ microgranite, quartz diorite, dacite, andesite, and minor rhyolite and rhyodacite (dacite predominant). Depletion of Nb relative to K and La concentrations are characteristics of the rocks, implying the magma was generated in a subduction zone environment. However, different from magma of other â€œnormalâ€ arcs that were derived from mantle wedges, the magma of the Sintang Intrusives was generated from subducted oceanic crust melting. The result of a careful study of trace element data show that the rocks are of adakite type, characterized by high Sr/Y and Zr/Sm ratios, moderate to strong fractionation of heavy rare earth elements (HREE) and absence of Eu anomalies suggesting melt extraction from garnet-amphibolite sources. By considering the tectonic development in the South China Sea and northwest Kalimantan, it is believed that the magma was probably originated from the melting of previously subducted South China sea oceanic crust (dead slab or fossil subduction) beneath Kalimantan continent in the Late Oligocene - Early Miocene. A compressive tectonic regime in Middle Oligocene, and possibly until Late Oligocene, led to crustal shortening and thickening that facilitated entrapment of arc magma in the Kalimantan crust. The fluid released caused by amphibole breakdown and may have been expelled from older amphibolebearing plutons during compressional tectonics would be significantly important for mineralization.Â Keywords : Kalimantan, Sintang Intrusives, oceanic crustal melting, mineralization